The effects of rice husk biochar rate on arbuscular mycorrhizal fungi and growth of soursop (Annona Muricata L.) seedlings - Harun, Nur Saidahtul Nadiah; Md. Jaafar, Noraini; Sakimin, Siti Zaharah (MDPI AG, 2021)
Soursop (Annona muricata L.) is increasingly planted in Malaysia for its agronomical importance as a multipurpose plant with medicinal and health benefits. However, there is limited information on soursop cultivation in Malaysia. Soursop can be inoculated with arbuscular mycorrhizal fungi (AMF) as a sustainable approach for successful seedlings growth before transplanting to field. As a beneficial symbiotic soil microorganism, AMF has been known as biofertilizer which can improve soil conditions and plant growth. Following the need to understand the soil management using soil beneficial microorganisms for soursop cultivation, this experiment aimed to determine the effects of AMF and biochar on the growth of soursop seedlings. The polybag experiment was conducted under glasshouse conditions at Farm 15, Faculty of Agriculture, UPM Serdang, Selangor. The study was arranged in Randomised Complete Block Design (RCBD) with eight treatments comprising different rates of rice husk biochar (RHB), with and without AMF and four replications. The treatments were; T1 (Control), T2 (AMF only), T3 (−AMF with 10 t/ha RHB), T4 (+AMF with 10 t/ha RHB), T5 (−AMF with 15 t/ha RHB), T6 (+AMF with 15 t/ha RHB), T7 (−AMF with 20 t/ha RHB) and T8 (+AMF with 20 t/ha RHB). Plant growth measurement were determined upon harvesting after four months of planting. Shoot and root biomass, leaf area meter, root surface area and root length were found significantly highest in soursop seedlings grown in soils amended with 10 t/ha RHB with or without AMF as compared to control. It was concluded that RHB, either individually or when in combination with AMF, had significantly improved the growth performance of soursop seedlings at nursery stage. Therefore, earliest inoculation of soursop seedlings with AMF at nursery stage could ensure successful mycorrhizal establishment and growth performance of soursop seedlings before transplanted under field condition.